2018
DOI: 10.2147/jaa.s160607
|View full text |Cite
|
Sign up to set email alerts
|

Methacholine challenge testing: comparative pharmacology

Abstract: Standardization of the methacholine inhalation challenge, the most common direct bronchoprovocation test, is important. One aspect of standardization is the appropriate washout period for pharmacologic agents which affect the response. This review summarizes the available data on pharmacologic inhibition of the methacholine response. Specific (anti-muscarinic) agents demonstrate marked bronchoprotection (up to 7 days for the long-acting drugs) which lasts longer than the duration of bronchodilation. The functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 58 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…Table 8 lists suggested withholding times for various bronchodilators. The withholding times are based on studies of the lasting bronchodilator effects of the various agents ( 93 , 94 ). Inhaled corticosteroids and leukotriene modifiers need not be withheld.…”
Section: Bronchodilator Responsiveness Testingmentioning
confidence: 99%
“…Table 8 lists suggested withholding times for various bronchodilators. The withholding times are based on studies of the lasting bronchodilator effects of the various agents ( 93 , 94 ). Inhaled corticosteroids and leukotriene modifiers need not be withheld.…”
Section: Bronchodilator Responsiveness Testingmentioning
confidence: 99%
“…It is a cholinergic agonist that acts on muscarinic receptors, mainly subtype M3 coupled to G protein, promoting a cascade of events that lead to the recruitment of calcium with consequent contraction of smooth muscle. 55 The contraction of airway smooth muscle promotes a decrease in diameter with a consequent increase in airway resistance. 55 MCh differs from ACh in terms of action time and selectivity, and it is degraded more slowly by acetylcholinesterase.…”
Section: Methacholinementioning
confidence: 99%
“…55 The contraction of airway smooth muscle promotes a decrease in diameter with a consequent increase in airway resistance. 55 MCh differs from ACh in terms of action time and selectivity, and it is degraded more slowly by acetylcholinesterase. In humans, MCh is often used in spirometry tests.…”
Section: Methacholinementioning
confidence: 99%
“…7 ► Not consume alcohol for at least 4 hours prior to the test. Reproduced from Davis et al 21 ICS, inhaled corticosteroids; LABA, long-acting beta-agonist; LAMA, long-acting muscarinic antagonist; SABA, short-acting beta-agonist; SAMA, short-acting muscarinic antagonist; uLABA, ultra-long-acting beta-agonist.…”
Section: General Proceduresmentioning
confidence: 99%
“…By studying airway smooth muscle contraction using methacholine challenge testing, Davis et al 21 showed the relative duration of bronchoprotection for a variety of commonly used respiratory medications. This gives some guide for the appropriate withhold times to establish clearance of these medications prior to testing when a baseline test (ie, without the support of medication) is required.…”
Section: General Proceduresmentioning
confidence: 99%